1976
DOI: 10.1083/jcb.71.2.341
|View full text |Cite
|
Sign up to set email alerts
|

5-bromodeoxyuridine may alter the differentiative program of the embryonic pancreas.

Abstract: The thymidine analog, 5-bromodeoxyuridine (BrdU), inhibits the differentiation of the acinar cells of the embryonic rat pancreas, while having little effect on the growth of the tissue. The BrdU-treated pancreas contains elevated alkaline phosphatase and carbonic anhydrase activities, and, unlike the normal pancreas, contains numerous extracellular fluid-filled vacuoles, surrounded by ductlike cells. Both alkaline phosphatase and carbonic anhydrase activities are located preferentially in the ductlike cells li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…How the transcription process manifests itself at the cellular level following BrdU exposure is, however, unclear. Various possibilities are outlined in the literature and may be arranged into three categories: 1) alteration in the cell cycle, which, in turn, would affect the growth and differentiation of the tissues (Bannigan and Langman, 1979;Bannigan, 1985Bannigan, , 1987; 2) chromosomal breakage (Kaback et al, 1964;Sutherland et al, 1985;Ackland et al, 1988); and 3) alteration in cytodifferentiation either directly or indirectly by affecting the cell membrane (Levis et al, 1971;Tsuboi and Baserga, 1973;Garcia et al, 1979;Maylie-Pfenninger and Jamieson, 19811, or the synthesis of extracellular matrix (Bischoff and Holtzer, 1970;Daniel, 1976;Ho et al, 1977;Giotta et al, 19801, or enzyme activity (Meuth and Green, 1974;Koyoma and Ono, 1971;Githens et al, 1977;Moscona and Moscona, 1979;Biggers et al, 1987). Bannigan and Langman (1979) and Bannigan (1985Bannigan ( , 1987 indicated that BrdU incorporation into DNA of the embryonic neuroepithelial cells resulted in the prolongation of the S-phase of the cell cycle, thus slowing the generation time and reducing the cell numbers, and eventually causing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…How the transcription process manifests itself at the cellular level following BrdU exposure is, however, unclear. Various possibilities are outlined in the literature and may be arranged into three categories: 1) alteration in the cell cycle, which, in turn, would affect the growth and differentiation of the tissues (Bannigan and Langman, 1979;Bannigan, 1985Bannigan, , 1987; 2) chromosomal breakage (Kaback et al, 1964;Sutherland et al, 1985;Ackland et al, 1988); and 3) alteration in cytodifferentiation either directly or indirectly by affecting the cell membrane (Levis et al, 1971;Tsuboi and Baserga, 1973;Garcia et al, 1979;Maylie-Pfenninger and Jamieson, 19811, or the synthesis of extracellular matrix (Bischoff and Holtzer, 1970;Daniel, 1976;Ho et al, 1977;Giotta et al, 19801, or enzyme activity (Meuth and Green, 1974;Koyoma and Ono, 1971;Githens et al, 1977;Moscona and Moscona, 1979;Biggers et al, 1987). Bannigan and Langman (1979) and Bannigan (1985Bannigan ( , 1987 indicated that BrdU incorporation into DNA of the embryonic neuroepithelial cells resulted in the prolongation of the S-phase of the cell cycle, thus slowing the generation time and reducing the cell numbers, and eventually causing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Dilution of the incorporated BrdU as a result of further division of the labeled cells during subsequent culture may also decrease the number of BrdUpositive cells in CHIBs, particularly after early-phase labeling. Moreover, BrdU may have a negative effect on pancreatic cell differentiation (35). Thus, the numbers of BrdU-labeled endocrine cells may underestimate the differentiation of initially proliferating ductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, BrdU became known as a differentiating agent owing to its effects on the morphology and phenotype of a wide range of cell types in vitro and in vivo, including normal chondrocytes, muscle, molar, brain, pancreatic and blood cells [15][16][17][18][19][20], and leukaemic and lung cancer cells [21][22][23][24]. More recently, the Ayusawa group [25,26] has reported that BrdU induces a senescent-like phenotype in both normal and transformed cells.…”
Section: Introductionmentioning
confidence: 99%